Dealing With Territorial Boundaries, Space, and Time in Robinson Crusoe and Life of Pi Novels (Postcolonial Perspective) - Magdalena Baga (TRANSBAHASA, 2024)
Today's globalization eliminates time, space, distance, and national barriers. The two novels examined in this study implied those issues. The objective of this study is to analyze the territorial boundaries, spatial dimensions, and temporal aspects that evoke a profound impact in Robinson Crusoe and Life of Pi, employing a postcolonial perspective. Both of these works originated from a shared concept, specifically the theme of being stranded as a result of a shipwreck. However, these novels were written throughout distinct times spanning several centuries. Robinson Crusoe was published in the 18th century, whilst Life of Pi was published during the 21st century. The similar concept of